Historical Study for the Differences of Processing of Pinellia ternata Tuber Between China and Japan - Liu, Yan; Ota, Misato; Fueki, Tsukasa; Makino, Toshiaki (Frontiers in Pharmacology, 2022)
Pinellia Tuber (the dried tuber of Pinellia ternata (Thunb.) Makino [Araceae]) (PT) is a crude drug used in traditional Chinese medicine (TCM) and Japanese Kampo medicine. PT is subjected to additional processing before use in TCM because of its toxic, while the processing has not been used in Kampo medicine. The aim of this study is to clarify the reason why the differences about the processing of PT between TCM and Kampo medicine have been appeared. We investigated successive literatures published in China and in Japan from the Han Dynasty to the modern age. The descriptions about the processing of PT in China had appeared since the Later Han dynasty as washing, and after that, various processing methods have been recorded, such as boiling, steaming, making cakes, and fermenting to prepare PT malt (PTM) with various drug additives. The objective of the processing for PT was not only to remove its toxicity but to change drug properties, and several kinds of processed PT had been developed to treat different types of "phlegm" in the Ming dynasty. The current Chinese Pharmacopoeia recommends the use of processed PT to avoid the toxicity, and registers unprocessed PT as well as three kinds of processed PT except for PTM which had been deleted in 2015 edition. These processing methods for PT have been established in the Qing dynasty. The oldest description in Japan was appeared in 1363, and the processing methods had been influenced by the literatures in the Song Dynasty. After that, the processed PT in Japan had mainly been PTM until the 18th century. In 1738, Shuan Kagawa wrote that PT should not be processed because its pharmacological effects disappeared and the toxicity of PT disappeared by preparing its decoction without processing. Then, the processing of PT has been unpopular, and the Japanese Pharmacopoeia has registered PT since 1939 without any processing. Compared to TCM, Japanese Kampo medicine has tended to avoid ideologism based on traditional knowledge and to adopt positivism. This policy has reflected the differences in the processing of PT between Kampo medicine and TCM.